Indoor positioning system for movement path analysis in healthcare institutions - Stefan Grönroos; Laura-Maria Peltonen; Valentin Soloviev; Johan Lilius; Sanna Salanterä (Finnish Social and Health Informatics Association, 2017)
In this paper, we describe an indoor positioning system designed to provide data on the movement patterns of hospital personnel. The data collection is ongoing and part of a larger study project, which aims to evaluate the impact of an information system implemented in a hospital setting. The indoor positioning system was designed to be non-intrusive and straightforward to deploy in multiple hospitals, while requiring minimal existing infrastructure. To this end, the system is based on battery-powered Bluetooth beacons, and mobile phones measuring the signal strength of the beacons to position their bearers. This paper describes the design and implementation of the system. We analyze the positioning accuracy of the system in order to evaluate its fitness for purpose. Based on the results, the system is suitable for short-term deployments due to its low cost and ease of installation.